Planowanie zapotrzebowania na pracę produkcyjną w warunkach zmienności i cykliczności popytu na produkty - Czerska, Małgorzata; Rutka, Ryszard (Employment Planning in the Conditions of Changeable Demand of Production, 2006)
Increasing globalization of economy intensifies the competition between producers of similar products. Price competition demands consistent adjusting of productive potential to changing needs. If the market of our products is flexible we need to use unconventional forms of hiring people. The paper presents process of employment planning in changeable demand of human work. It identities main tasks and procedure of new and unconventional form of hiring people in the area of production.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 251-261